Exploring the Evolution of Inquisitiveness in Education: A Bibliometric Perspective Over the Last Decade - Hadi, Fida Rahmantika; Mulyadi, Mulyadi (LP. Ma'arif Janggan Magetan, 2025)
This study performs a bibliometric analysis of research trends of inquisitiveness in learning over the past decade. The background of the research highlights the complexity of educational challenges in the era of technology and information, where the inquisitiveness of learners becomes crucial in shaping character, skills, and attitudes. For the research method, this study employed a bibliometric approach with data garnered from Dimension AI. The data collection process identified 157 publications in the form of articles and proceedings related to inquisitiveness in educational journals from 2015 to 2024. The results of data analysis using VOSviewer show a positive trend in inquisitiveness research interest. Citations from these studies show the complexity of relationships between studies, while the distribution of publications between countries forms clusters reflecting the level of international collaboration. The focus of research on the topic of inquisitiveness includes 1) experience and child, 2) factors and models, 3) critical thinking disposition and self-confidence, 4) curiosity and emotional intelligence, and 5) playfulness. Indicate the main conclusions or interpretations. This research provides in-depth insights into the development of scientific literature related to inquisitiveness in learning, providing a basis for the design of more effective learning strategies to increase the inquisitiveness of learners in the modern education era.